Raw turmeric and pure curcumin: a comparison of embryonic cytotoxicity in zebrafish - Rajagopal, Raskin Erusan; Balasubramanian, Meenakshi; Kalyanaraman, Shantaraman (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Turmeric (Curcuma longa) is widely used in ayurveda and siddha formulations for treating various ailments. This study compares the gross effects of curcumin and natural state turmeric on zebrafish embryos. Methods: Turmeric powder and curcumin were used in this study. Zebrafish embryos were treated with different concentration of both turmeric and curcumin to evaluate their gross effects including toxicity. Morphological variations including hatching, survival, heart rates, head width, eye width, tail width and yolk sac area were examined by stereomicroscope. Results: Embryos treated with curcumin or raw turmeric with concentration of 27.628 and 36.83µg/ml exhibited a reduction of survival rates (15-20%) at 24, 48 and 72hpf. Turmeric treated embryos had near normal hatching rates when compared to curcumin treated embryos at 48hpf whereas decreased hatching rate was observed in turmeric treated groups at 72hpf when compared to curcumin treated group. No significant morphological anomaly in head /eye / tail width, length of yolk sac and average embryo length were witnessed among all the 3 groups. The toxicity assays revealed various morphological deformities in embryos treated with different concentrations of both turmeric and curcumin. Conclusions: Zebrafish embryos treated with increasing concentrations of curcumin in pure form or raw turmeric exhibited similar morphometric and toxic effects indicating that raw turmeric could elicit anti cancer activity with similar potency as that of active ingredient curcumin due to their toxicity attribute. It may be beneficial to explore the negative attributes of such common natural food ingredients that may be beneficial for therapeutic interventions.